Report on proposed new interior design scheme for Nik Erwan Roseli Boutique, at Lot 93, Jalan Maarof, Off Jalan Bangsar, 59100 Kuala Lumpur / Rash Eedzwan Abdul Rashid - Abdul Rashid, Rash Eedzwan (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose new interior design scheme for Nik Erwan Roseli Boutique at lot 93, Jalan Maarof, Off Jalan Bangsar, Kuala Lumpur. This proposed ready wear boutique is to attract users, especially all the from any race to try for all the dress by the designer. Most of dress design for casual wear. The target customer is mostly from VIP person. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the business in the boutique. Besides, the concept and images itself should be also related with the theme of the boutique. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.